INFORMATIVENESS OF CLASSIFICATION CRITERIA FOR NASSELLARIA (RADIOLARIA): THE FAMILY LAMPROCYCLIDAE - Tochilina S.V.; Kosenkova S.T. (My University, 2001)
It is known that many morphological types of radiolarians from the World Ocean remained stable from the Mesozoic to the Present. Radiolarians whose skeletons consist of three parts are an example of such a stable morphotype These are represented by the genera Tricolocapsa, Theocapsa, Sethocapsa, Theoconus, Theocyrtis Lamprocyclas Lamprocyrtis, Theocorythium, and others. However, a wide diversity in the shape and size of each part and in the arrangement of the rays in the cephalis are responsible for numerous errors in taxonomic determination. Many aspects of this problem may be tackled by using mathematical methods and computers. A statistical method for pattern recognition is applied in this paper to classify Nassellaria specimens on the basis of a combination of variables. The results of this classification are discussed to show that the measurements of skeletal elements are a major factor in radiolarian taxonomy, whereas their ratios constitute characters that indicate the affinity and evolutionary lines of radiolarians.
Keywords: Mesozoic; Mesozoic; Мезозой